2019
DOI: 10.23960/jpf.v9.n1.202107
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Discovery Learning-based Module to Improve Students’ Scientific Literacy

Abstract: In learning science, it is necessary to have a learning model that can integrate scientific literacy skills. This study aimed to develop discovery learning-based module to improve students’ scientific literacy. We used R & D research that adapts the 4-D model device development procedure, namely define, design, develop, and disseminate. Product assessment was carried out after revision stage I by 3 media experts, 3 material experts, and 1 SMA YPPK Taruna Bakti teacher. To determine student responses, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Discovery learning model is more dominant in developing students' problem-solving skills both students who come from urban or coastal compared to RQA or conventional models, this is because the discovery model implements team learning in analyzing and solving problems [59], [60], [61] there is a syntax for find solutions to the problems being faced [51], [53], [62] and students are trained to become experts and adult learners in solving real-life problems [60], [63]. Discovery learning model is able to provide an increase in students' problem-solving skills, this can be noticed from the increase before and after learning with discovery models [64]. The model is able to provide space for students to hone skills in finding solutions to the problems provided [65]- [67].…”
Section: Discussionmentioning
confidence: 99%
“…Discovery learning model is more dominant in developing students' problem-solving skills both students who come from urban or coastal compared to RQA or conventional models, this is because the discovery model implements team learning in analyzing and solving problems [59], [60], [61] there is a syntax for find solutions to the problems being faced [51], [53], [62] and students are trained to become experts and adult learners in solving real-life problems [60], [63]. Discovery learning model is able to provide an increase in students' problem-solving skills, this can be noticed from the increase before and after learning with discovery models [64]. The model is able to provide space for students to hone skills in finding solutions to the problems provided [65]- [67].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis conducted was the effectiveness of the android-assisted discovery learning model to improve students' scientific literacy. Based on the results of a review of the articles in Table 1, it was found that the discovery learning model can improve students' scientific literacy skills (Bahtiar et al, 2022;Berliana et al, 2023;Budiarti et al, 2021;Maghfiroh et al, 2023;Priadi et al, 2022;Purnamawati &;Basuki, 2021;Rahmawati et al, 2023;Warlinda et al, 2022;Widiyana et al, 2021;Winarni et al, 2020;Yolida et al, 2022). The discovery learning model is a model that requires students to find their concepts through a series of activities they do.…”
Section: Discussionmentioning
confidence: 99%
“…Developing physics e-modules based on discovery learning is efficacious in improving students' scientific literacy skills Warlinda et al (2022). Applying the guided discovery learning model with the SETS approach supported by the chemistry e-module significantly influences the scientific literacy of SHS 1 Padang grade XI students Budiarti et al (2021).…”
mentioning
confidence: 99%